If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5t + 20t + 15 = 3t + 3 Reorder the terms: 15 + -5t + 20t = 3t + 3 Combine like terms: -5t + 20t = 15t 15 + 15t = 3t + 3 Reorder the terms: 15 + 15t = 3 + 3t Solving 15 + 15t = 3 + 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. 15 + 15t + -3t = 3 + 3t + -3t Combine like terms: 15t + -3t = 12t 15 + 12t = 3 + 3t + -3t Combine like terms: 3t + -3t = 0 15 + 12t = 3 + 0 15 + 12t = 3 Add '-15' to each side of the equation. 15 + -15 + 12t = 3 + -15 Combine like terms: 15 + -15 = 0 0 + 12t = 3 + -15 12t = 3 + -15 Combine like terms: 3 + -15 = -12 12t = -12 Divide each side by '12'. t = -1 Simplifying t = -1
| -3(z+4)+6=6z+21 | | 0.65a=0.52 | | 20x^3+84x^2+72x=0 | | 5v^2+4v+3=0 | | -(8-3b)=15b+28 | | -2t+3(2+t)=17 | | 2*-3-3y=6 | | 3(4x+1)=6-5(4x-3) | | -n=287.658 | | 2x=685+85 | | x/14=28 | | 3+6x=6+2x | | 3x-1+3x=13x+7+x | | 16x^3-54y^3=0 | | y-1=-(x-3) | | y-4=x+2 | | 3x-1+3x=13+7+x | | 5(-5v-2)=-5(v+2) | | x+(x+3)=1.70 | | t-w=masolvew | | 51-11x=19+5x | | 0=2y-3x-8 | | 8m+8=4m-4 | | 7(3+2v)+2(-8v-8)=1-8v+8v-8 | | -14-n=87 | | x+42+140=180 | | 9x-14=4x+21 | | 1/3x-4=5 | | .5+2(0)=7 | | 600-z=234 | | 7z-1=47+3z | | 4(a+4)-3=34 |